Accurate estimation of cell-type composition from gene expression data - Daphne Tsoucas (Nature Portfolio, 2019)
Bulk RNA-seq data harbors valuable information about gene expression levels from different cell types in tissue samples. Here, the authors develop DWLS, a computational method for estimating cell-type composition of bulk data by leveraging single-cell RNA-seq-derived cell-type signatures.